Developmental trajectories for young children with 16p11.2 copy number variation. Issue 4 (27th March 2017) - Bernier, Raphael; Hudac, Caitlin M.; Chen, Qixuan; Zeng, Chubing; Wallace, Arianne Stevens; Gerdts, Jennifer; Earl, Rachel; Peterson, Jessica; Wolken, Anne; Peters, Alana; Hanson, Ellen; Goin‐Kochel, Robin P.; et al.
Abstract : Copy number variation at 16p11.2 is associated with diverse phenotypes but little is known about the early developmental trajectories and emergence of the phenotype. This longitudinal study followed 56 children with the 16p11.2 BP4‐BP5 deletion or duplication between the ages of 6 months and 8 years with diagnostic characterization and dimensional assessment across cognitive, adaptive, and behavioral domains. Linear mixed modeling revealed distinct developmental trajectories with deletions showing VIQ gains but declines in motor and social abilities while duplications showed VIQ gains and steady development across other domains. Nonparametric analyses suggest distinct trajectories and early cognitive abilities for deletion carriers who are ultimately diagnosed with intellectual disability and developmental coordination disorder as well as distinct trajectories and early social communication and cognitive abilities for duplication carriers diagnosed with ASD and intellectual disability. Findings provide predictions for patient developmental trajectories, insight into mean functioning of individuals with 16p11.2 at early ages, and highlight the need for ongoing monitoring of social and motor functioning and behavioral symptomatology to improve treatment planning. © 2017 Wiley Periodicals, Inc.